Utility of Medical Instruments in Nadi Pareeksha: A Critical Review - Prasad, Anu S; Katti, Anand (International Research Journal of Ayurveda & Yoga, 2022)
Acharya’s who are considered as apta have explained well about importance of nadi pareeksha in diagnosis of disease in classical books of Ayurveda. Yoga ratnakara, Sarangadara samhitha, Bsavarajeeyam, Bava prakasha have mentioned about nadi pareeksha in Ayurveda. By the nadi pareeksha one can get so many factors such as Gati,Vega, Sthiratwa,Katinyata of the nadi and by the proper examination one will be able to diagnose the disease. Nadi pareeksha can be correlated to the pulse examination and now days the concept of relation between pulse wave velocity and heart disease has gained much attention and being analyzed so proper nadi pareeksha becomes more important. In this background the present article discusses the need of a proper instrument for examining nadi and comparison of existing two such instruments.